Active-passive combined and closed-loop control for the thermal management of high-power LED based on a dual synthetic jet actuator. (15th January 2017) - Deng, Xiong; Luo, Zhenbing; Xia, Zhixun; Gong, Weijie; Wang, Lin
Highlights: An active-passive combined heat dissipation method based on a DSJA is proposed. Nine thermal management schemes are investigated for high-power LED cooling. The combination method can enhance heat dissipation and reduce installation space. A closed-loop control system is developed for high-power LED thermal management. Abstract: In order to better solve the thermal management of high-power LED and facilitate its miniaturization, an active-passive combined heat dissipation method based on a dual synthetic jet actuator (DSJA) is proposed. Comparative analyses on heat dissipation characteristics and installation-space reductions of nine thermal management schemes are carried out. The results indicate that the temperature rapidly decreases and stabilizes once the actuator is activated. The heat dissipation effect based on DSJA is better than that based on synthetic jet actuator (SJA). The combination method with the vertical layout of DSJA makes the stable temperature of the LED and the installation space decrease 16 °C and 72.3% with respect to the commercial heat sink. Furthermore, a closed-loop system based on the combination method is developed to realize the autonomous control of the LED temperature within a setting temperature range. It is concluded that the operation duty cycle (ODC) reduces with the increase of the upper limit temperature, and there is an optimal impingement distance where the ODC is lowest of 29.1%. The closed-loop control will be greatly useful for the adaptive thermal management of electronic devices.